2017
DOI: 10.1063/1.5000959
|View full text |Cite
|
Sign up to set email alerts
|

Observation of enhanced magnetic transition in Pbnm SmFeO3

Abstract: Abstract:Rare-earth orthoferrites RFeO3 materials have recently attracted a great attention for their intriguing technolgical potential. Among these materials, SmFeO3 holds great promise not only for the excellent physical properties (fast magnetic switching, spin reorientation and magnetization reversal) but also for its potential ferroelectric properties which have been recently under debate. Here we focus our attention on T-dependent Zero Field Cooled (ZFC) and Field Cooled (FC) magnetization properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…6B and C), with a magnetization peak at approximately 150 K, which could be ascribed to a transition in the magnetic structure of the SmFeO 3 phase induced by the Sm magnetic moments (antiferromagnetic exchange interaction between the two magnetic sublattices). 17,18 On the basis of the XRD measurements in Fig. 4, no contribution was detected from other iron oxide phases.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…6B and C), with a magnetization peak at approximately 150 K, which could be ascribed to a transition in the magnetic structure of the SmFeO 3 phase induced by the Sm magnetic moments (antiferromagnetic exchange interaction between the two magnetic sublattices). 17,18 On the basis of the XRD measurements in Fig. 4, no contribution was detected from other iron oxide phases.…”
Section: Resultsmentioning
confidence: 89%
“…12,13 In addition to these important studies, recent reports have shown that creating direct interfaces between iron-based oxides and carbon materials can allow possible rehybridization effects with signicant benets not only for the control of sp 3 -rich characteristics of the carbon layers but also for applications in electrical-memory devices. [14][15][16][17][18] In this context, rare-earth orthoferrites RFeO 3 (R ¼ rare-earth ion) are a new class of materials with a distorted perovskite Pbnm structure which intrinsically exhibit canted ferromagnetism due to the presence of the 4f-electrons and 3d-electrons sublattices. 19 These materials have recently attracted signicant attention for their important application perspectives in magnetic, ferroelectric and multiferroic devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations